Phenotypic and functional heterogeneity of monocytes in health and cancer in the era of high dimensional technologies. (March 2023) - Guglietta, Silvia; Krieg, Carsten
Abstract: Monocytes have been traditionally classified in three discrete subsets, which can participate in the immune responses as effector cells or as precursors of myeloid-derived cells in circulation and tissues. However, recent advances in single-cell omics have revealed unprecedented phenotypic and functional heterogeneity that goes well beyond the three conventional monocytic subsets and propose a more fluid differentiation model. This novel concept does not only apply to the monocytes in circulation but also at the tissue site. Consequently, the binary model proposed for differentiating monocyte into M1 and M2 macrophages has been recently challenged by a spectrum model that more realistically mirrors the heterogeneous cues in inflammatory conditions. This review describes the latest results on the high dimensional characterization of monocytes and monocyte-derived myeloid cells in steady state and cancer. We discuss how environmental cues and monocyte-intrinsic properties may affect their differentiation toward specific functional and phenotypic subsets, the causes of monocyte expansion and reduction in cancer, their metabolic requirements, and the potential effect on tumor immunity.